MULHERES EM TRÂNSITO: MOTIVAÇÕES PARA O TRÂNSITO RELIGIOSO DE MULHERES A IGREJAS ORGÂNICAS - MACIEL, REBECCA FERREIRA LOBO ANDRADE (2018)
In the 1980s, publications emerged from a social need to understand what was happening in the religious field, where Catholicism lost its hegemony and new religious experiences gained strength. In this context, the concept “religious transit” arises as a way to theorize about the new form of spirituality that people were building: more individualized, subjective and, mainly, transitory. However, in the development of studies on religious transit in Brazil, some important aspects were left aside, such as gender, race and class relations. The religious trajectories change according to the subjects under analysis and this can be clearly perceived in the case of women. Recent researches indicate that men and women have different motivations for religious transit. In the case of organic churches, this transit passes through areas that have not yet been investigated by the scholars. Because they are churches in domestic and public spaces, without connection to evangelical denominations, they become a refuge place for women who wish to leave their institutional environment. Therefore, we need to understand to what extent women's adherence to organic churches is motivated by gender issues. Our goal is to analyze the relationship between gender demands and women's adherence to organic churches. For this, we analyzed a vast bibliographical material to understand religious mobility in Brazil, with a special focus on women’s movements and their motivations for joining organic churches. Likewise, online questionnaires with 17 quantitative and qualitative questions were applied throughout Brazil to obtain new statistical data about this subject.